2018
DOI: 10.1007/s11469-018-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness in Schools: a Health Promotion Approach to Improving Adolescent Mental Health

Abstract: Between 10 and 20% of adolescents worldwide experience a mental health problem within a given 12-month period. Mental health problems impact on an adolescent's potential to live a fulfilling and productive life and lead to challenges such as stigma, isolation and discrimination. To address this need, in recent years, there has been growing interest into broad-based school-integrated health promotion interventions that seek to build resilience and augment protective factors in adolescents. Mindfulness-based int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 35 publications
1
34
0
1
Order By: Relevance
“…The school-based MBIs included in the present review also appeared to augment students' capacity for coping with the challenges associated with child and adolescent transition (i.e., the third Master theme to emerge from the dataset). Indeed, elsewhere researchers have highlighted both the immediate and preventative applications associated with learning mindfulness prior to adulthood (e.g., Sapthiang et al 2018). In the present systematic review, improvements in coping skills were also reported to positively impact on social skills.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The school-based MBIs included in the present review also appeared to augment students' capacity for coping with the challenges associated with child and adolescent transition (i.e., the third Master theme to emerge from the dataset). Indeed, elsewhere researchers have highlighted both the immediate and preventative applications associated with learning mindfulness prior to adulthood (e.g., Sapthiang et al 2018). In the present systematic review, improvements in coping skills were also reported to positively impact on social skills.…”
Section: Discussionmentioning
confidence: 49%
“…In addition to seeking to enhance mental illness treatment approaches for young people, there is growing awareness of the benefits of cultivating resiliency and protective traits (Sapthiang et al 2019b;Schonert-Reichl and Lawlor 2010;Windle 2011). Accordingly, the UK government has made mental health promotion a priority area and has emphasised the important role of schools for improving young people's mental health (Sapthiang et al 2018). Indeed, since most children spend a considerable amount of time at school, it is a viable setting for cultivating protective traits (e.g., emotional literacy, coping skills) (Van Gordon et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach with potential for use as a communitylevel preventative interventional strategy for reducing adolescent gambling is mindfulness, which has been the subject of increased empirical attention in recent years (Sapthiang et al 2018). Mindfulness is a form of meditation that involves cultivating present moment awareness as a means of increasing perceptual distance from gambling urges, as well as from distressing emotions and maladaptive cognitive processes more generally (Griffiths et al 2016).…”
Section: Community-level Health Promotion Approachesmentioning
confidence: 99%
“…[7] The socio-ecological model highlights the need for joint care pathways in receiving countries, whereby child and adolescent psychological health services actively collaborate with social care services, nongovernmental organizations, and also community-level stakeholders such as schools. [12] Effective joint care pathways help to foster knowledge and best practice sharing and can limit delays in young refugees gaining access to education, housing, and health-care support services. [7] Furthermore, such collaborative multiagency approaches are also in the interests of tailoring refugee mental health support provision to meet the specific needs of child and adolescent service users.…”
Section: Key Mental Health Issuesmentioning
confidence: 99%